The Influence of Learning Independence and Self-efficacy on Students' Mathematical Understanding Ability Based on Kinach’s Theory - Jaenudin Darwati; Elsa Komala; Muhamad Soeleman (Universitas Suryakancana, 2026)
This study aims to analyze the influence of learning independence and self-efficacy on students’ mathematical understanding ability based on Kinach’s theory. This study employs a quantitative approach with data analysis techniques consisting of simple linear regression and multiple linear regression. The study population includes all 10th-grade students at state Islamic senior high schools (MA Negeri) in Cianjur Regency, with a sample of 34 students from class XA selected through purposive sampling. The instruments used consist of a mathematical understanding ability test based on Kinach’s theoretical indicators in the topic of Arithmetic Sequences and Series, as well as questionnaires on learning independence and self-efficacy. The data were analyzed using simple and multiple linear regression tests, preceded by prerequisite tests including normality, linearity, heteroscedasticity, and multicollinearity. The results show that learning independence has a positive and significant influence on students’ mathematical understanding ability based on Kinach’s theory, with a contribution of 36.3%. Likewise, self-efficacy has a positive and significant influence, contributing 69.4%. Furthermore, learning independence and self-efficacy simultaneously have a significant influence on students’ mathematical understanding ability based on Kinach’s theory, with a combined contribution of 69.7%. These findings indicate that the higher the students’ levels of learning independence and self-efficacy, the better their mathematical understanding ability as conceptualized in Kinach’s theory.